EXPERIMENTAL INVESTIGATIONS OF HORIZONTAL LATERAL STIFFNESS OF RAILS UNDER DIFFERENT DESIGNS OF RAIL FASTENERS - Velinets, V. P. (Science and Transport Progress, 2015)
Purpose. Calculation of a railway track on the strength is one of the sections of the overall complex research problems of interaction track and rolling stock. This paper describes the experimental study of horizontal transverse stiffness of railway rails with various strands of rail fasteners. Materials of this article should be relevant and will make it possible to calculate the strength of railway track using the correct and corrected performance of horizontal transverse stiffness of rail threads. Methodology. Determination of horizontal transverse rigidity of rail yarns with different designs of rail fasteners was conducted by measuring the quantities of transverse displacement of rails calculation points – namely the head and sole. For research the specialist equipment was created, made up of lineside jack DC-20, equipped with a hydraulic pressure gauge to measure pressure and rigid rod for horizontal rail stop in the thread, the opposite of the jack. Lateral movement of the head and sole of the track were recorded, and measured with indicators of clock type within a few hundredths of a millimeter. The horizontal lateral load on the rail jack was created by the injection pressure in the cylinder which was fixed with manometer into the jack. Load of rails was conducted over 2 tons of degrees ranging from 0 to 8 tons. To obtain reliable measurement results of lateral movement of the head and the base rails, its movement was conducted for each type fasteners not less than in 3 sections. Measurements were carried out without the creation of vertical load. Findings. With the developed method was found transverse displacement magnitude of rails calculation points at different designs of rail fasteners. Originality. The experimental studies were first found the mentioned horizontal transverse stiffness of rail threads in the head and sole of modern designs for different rail fasteners. Practical value. The values of horizontal transverse stiffness of rail threads in the head and sole of modern designs for different rail fasteners that were found by the author make it possible to calculate the strength of railway track using correct and corrected values of these characteristics.